IDDF2020-ABS-0015 Prucalopride in the treatment of chronic GERD. (18th November 2020) - Shivam, Shivam; KN, Manohar
Abstract : Background: Treatment of persistence of gastroesophageal reflux disease (GERD) symptoms, despite readily available medications and lifestyle advocation is challenging. Prucalopride, a selective high-affinity serotonin (5-HT4 ) receptor agonist, has been a good therapeutic alternative. Data from large randomized, controlled clinical trials indicate that it is effective in chronic constipation and offers a new therapeutic alternative for those whose condition fails to respond to conventional laxatives. Clinical use of Prucalopride in GERD has been of immense use in patients refractory to the conventional pharmacological treatments. Methods: A 45-year-old type 2 diabetic, chronically constipated male gastroesophageal reflux disease-patients presented to our outpatient department with reflux symptoms and an increased number of reflux episodes. Gastroesophageal reflux was detected by multichannel impedance (MII) monitoring. He had been prescribed Pantoprazole and domperidone for his symptoms in the past but did not get relieved. We treated him with prucalopride (2 mg/day). The second MII-monitoring after the initiation of prucalopride 2 mg per day (plus pantoprazole 40 mg per day) showed an overall decrease in reflux episodes. Results: Numbers of all reflux episodes, as well as non-acid reflux episodes, were reduced in the patients. The objective findings were concordant with subjective reports of symptomatic relief. There were no major adverse events during therapy with prucalopride. Conclusions: Administration of prucalopride showed promising results in the treatment of persisting or weakly and/or non-acid reflux episodes in this chronically constipated patient. Therefore, prucalopride can be regarded as a good therapeutic option in the treatment of standard proton pump inhibitor-persistent reflux in the chronically constipated patients.